Positioning of periodic AlN/GaN multilayers: Effect on crystalline quality of a-plane GaN - Kamarudzaman, Anas; Shuhaimi, Ahmad; Azman, Adreen; Omar, Al-Zuhairi; Supangat, Azzuliani; Talik, Noor Azrina (Elsevier, 2020)
We report the effect of 40 pairs of periodic AlN/GaN multilayers on the a-plane undoped-gallium nitride (ud-GaN) grown on r-plane flat sapphire substrate via metal-organic chemical vapor deposition. The influence of the position of the periodic AlN/GaN multilayers was seen to enhance the crystalline quality and surface morphology of the a-plane ud-GaN. The surface morphology analysis via atomic force microscopy has shown that the surface roughness was as low as 1.01 nm upon the insertion of the 40 pairs of periodic AlN/GaN multilayers with an optimum position. The on- and off-axis x-ray ω-scan rocking curves illustrate the enhancement in crystalline quality with a reduction of the full width at half maximum from 0.34° to 0.25° along [0001] direction and 0.91°–0.47° along [1–100] direction. The grown a-plane GaN with periodic AlN/GaN multilayers was seen to exhibit different relaxation strain states at different position as seen from the Raman spectroscopy. Room-temperature photoluminescence spectra shows that the sample with optimum periodic AlN/GaN multilayers position exhibits the lowest yellow and blue luminescence band. © 2019